Analisis Kinerja Mesin Pencacah Plastik Berbasis Pisau Berputar - Nasution, Heri Prinando; Ramadhan, Alfian; Hermanto, Tino; Iswandi, Iswandi; Darianto, Darianto (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
Plastic waste is one of the most significant contributors to waste production in Indonesia, reaching 65.2 million tons per year. Efforts to reduce waste volume are carried out by shredding plastic into smaller sizes to facilitate recycling. This study aims to analyze the production capacity, quality, and efficiency of a rotating blade-based plastic shredding machine and to determine the necessary maintenance to sustain its long-term performance. The method employed is a quantitative approach, which involves recording and analyzing data from machine tests using 10 samples of HDPE and PP plastic. The results indicate that the machine's production capacity for HDPE plastic is 3.43 kg/min, while for PP plastic, it is 1.42 kg/min. The study concludes that the rotating blade-based plastic shredding machine is effective in processing plastic waste, with results varying based on the type of plastic material.